Long and short‐term assessment of surface area changes in saline and freshwater lakes via remote sensing - Yagmur, Nur; Bilgilioglu, Burhan Baha; Dervisoglu, Adalet; Musaoglu, Nebiye; Tanik, Aysegul (Wiley, 2020)
AbstractAdvances in remote sensing technology enable monitoring and detection of these vulnerable water bodies that bear numerous functions and ecological services beyond their intended use. As such, valuable data and information may be provided for long and short‐term analyses and stored in a database for future projections. This paper initially grouped 18 natural lakes of the Konya Closed Basin of Turkey according to their salinity level. Freshwater, saline and brackish lakes have then undergone temporal analysis for every 5‐year intervals via Landsat satellite images. Freshwater lake surfaces have not changed noticeably during the inspection period; however, saline waters have decreased in surface area by 32%. Beysehir Lake constituting 94% of the freshwater category and Tuz Lake representing 97% of the saline group were selected for the short‐term analysis that was monthly conducted for years 2017 and 2018 with optical and SAR images to better verify cause and effect relationship.